Open space management in residential areas – how it is organised and why - Lindgren, Therese; Castell, Pål (International Journal of Strategic Property Management, 2010)
Housing companies manage a considerable proportion of urban open green space in Sweden. This article explores how 62 Swedish housing companies, municipal and private, organise their open space maintenance and the reasons behind organisational structure. Here, organisational structure covers three aspects of open space maintenance: (1) whether performed in‐house or by a contractor, (2) whether performed by local managers or circulating teams, and (3) whether and how residents are involved in management. The organisational structures varied widely among the housing companies studied. Mixed structures were common. Formal resident involvement processes were almost only found in municipally owned areas with local managers. The arguments could be derived from two general management approaches, prioritizing either customer relations more or economic efficiency. The conclusion was that management approach might be important in choosing organisational structure.First published online: 18 Oct 2010